Effects of chronic Δ9-tetrahydrocannabinol treatment on Rho/Rho-kinase signalization pathway in mouse brain - Halil Mahir Kaplan; Percin Pazarci (Elsevier, 2017)
Δ9-Tetrahydrocannabinol (Δ9-THC) shows its effects by activating cannabinoid receptors which are on some tissues and neurons. Cannabinoid systems have role on cell proliferation and development of neurons. Furthermore, it is interesting that cannabinoid system and rho/rho-kinase signalization pathway, which have important role on cell development and proliferation, may have role on neuron proliferation and development together. Thus, a study is planned to investigate rhoA and rho-kinase enzyme expressions and their activities in the brain of chronic Δ9-THC treated mice. One group of mice are treated with Δ9-THC once to see effects of acute treatment. Another group of mice are treated with Δ9-THC three times per day for one month. After this period, rhoA and rho-kinase enzyme expressions and their activities in mice brains are analyzed by ELISA method. Chronic administration of Δ9-THC decreased the expression of rhoA while acute treatment has no meaningful effect on it. Administration of Δ9-THC did not affect expression of rho-kinase on both chronic and acute treatment. Administration of Δ9-THC increased rho-kinase activity on both chronic and acute treatment, however, chronic treatment decreased its activity with respect to acute treatment. This study showed that chronic Δ9-THC treatment down-regulated rhoA expression and did not change the expression level of rho-kinase which is downstream effector of rhoA. However, it elevated the rho-kinase activity. Δ9-THC induced down-regulation of rhoA may cause elevation of cypin expression and may have benefit on cypin related diseases. Furthermore, use of rho-kinase inhibitors and Δ9-THC together can be useful on rho-kinase related diseases.